2011
DOI: 10.1111/j.1600-0684.2011.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful implementation of cooperative handling eliminates the need for restraint in a complex non‐human primate disease model

Abstract: Introduction Streptozotocin-induced diabetic nonhuman primates are used to study efficacy and safety of innovative immunosuppression after islet transplantation. We implemented a training program for medical management of a chronic disease state. Methods Cooperation with hand feeding and drinking; shifting; and limb presentation were trained utilizing predominately positive but also negative reinforcement in 52 animals compared with 28 macaques subjected to conventional physical and/or chemical restraint. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 46 publications
0
53
0
Order By: Relevance
“…These metabolic models rely on stress-sensitive outcome measures, primarily blood glucose and insulin secretory capacity, and therefore stress should be kept minimal. In NHPs it has been shown that stress resulting from restraint can impair glucose tolerance and significantly increase blood glucose levels: this contrasts with cooperative handling that preserves normal pathophysiological features (Lapin et al, 2013;Shirasaki et al, 2013;Graham et al, 2012b).…”
Section: Experimental Handling In T1d Modelsmentioning
confidence: 91%
See 1 more Smart Citation
“…These metabolic models rely on stress-sensitive outcome measures, primarily blood glucose and insulin secretory capacity, and therefore stress should be kept minimal. In NHPs it has been shown that stress resulting from restraint can impair glucose tolerance and significantly increase blood glucose levels: this contrasts with cooperative handling that preserves normal pathophysiological features (Lapin et al, 2013;Shirasaki et al, 2013;Graham et al, 2012b).…”
Section: Experimental Handling In T1d Modelsmentioning
confidence: 91%
“…In the case of the NHP, vascular access ports are recommended to enable frequent blood sampling and intensive fluid management protocols in the familiar homecage, to avoid additional stressors and separation from the social cohort (Graham et al, 2009(Graham et al, , 2010. This should be combined with training for cooperative handling, also with the aim to avoid stressful situations especially in the case of animal wellbeing, and to enable the early detection of discomfort in animals so that an early and quick intervention can be started (Graham et al, 2012b).…”
Section: Experimental Handling In T1d Modelsmentioning
confidence: 99%
“…Animals were pair‐housed with compatible conspecifics and participated in an environmental enrichment program designed to encourage sensory engagement, enhance foraging behavior, novelty seeking, promote mental stimulation, increase exploration, play and activity levels, and strengthen social behaviors, together providing opportunities for animals to increase time‐budget spent on species typical behaviors. Animals were trained to cooperate in medical procedures including hand feeding and drinking, shifting into transport cages for sedation, and presentation for blood collection, drug administration, and examination …”
Section: Methodsmentioning
confidence: 99%
“…4). We have eliminated stress related to intense handling by implementing animal refinement programs, so that physical and chemical restraint is no longer applied [20]. STZ protocols that are adjusted to recipient characteristics avoid renal toxicity with the consequence of protein wasting via the urine, especially when nephrotoxic drugs such as calcineurin inhibitors are used in concert with a nephrotoxic insult sustained from diabetes induction with STZ.…”
Section: Bw Loss and Causative Factorsmentioning
confidence: 99%